2021
DOI: 10.3389/fnut.2021.676026
|View full text |Cite
|
Sign up to set email alerts
|

Food Sources Contributing to Intake of Choline and Individual Choline Forms in a Norwegian Cohort of Patients With Stable Angina Pectoris

Abstract: Background: Choline is an essential nutrient involved in a wide range of physiological functions. It occurs in water- and lipid-soluble forms in the body and diet. Foods with a known high choline content are eggs, beef, chicken, milk, fish, and selected plant foods. An adequate intake has been set in the US and Europe, however, not yet in the Nordic countries. A higher intake of lipid-soluble choline forms has been associated with increased risk of acute myocardial infarction, highlighting the need for knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
(50 reference statements)
1
17
0
Order By: Relevance
“…In contrast, Nagata et al [ 42 ] did not find any association between PtC and CVD deaths in Japanese adults. The distribution of individual choline form intakes found in this cohort is consistent with the pattern reported in the Norwegian cohort [ 38 ]. In the current study, an inverse association between dietary FC and CVD but not the other forms of choline was detected.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, Nagata et al [ 42 ] did not find any association between PtC and CVD deaths in Japanese adults. The distribution of individual choline form intakes found in this cohort is consistent with the pattern reported in the Norwegian cohort [ 38 ]. In the current study, an inverse association between dietary FC and CVD but not the other forms of choline was detected.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, due to variation in the number of FFQ items, intake of choline and betaine may not be similar between studies [ 36 ]. In addition, discrepancies in dietary assessment tools, adjusting for total energy, dietary pattern, and characteristics of the population, may be involved in different observed values among studies [ 38 ]. According to the National Academies of Medicine (NAM), the recommended adequate intake (AI) for choline is 550 and 425 mg/d for males and females, respectively [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important because previous global studies did not calculate the country-specific production amounts of PUFAs and choline ( 24 , 34 ). An assessment based on the National Health and Nutrition Examination Survey (2009–2012 NHANES) found that the choline intake levels are well below the recommended levels in around 90% of Americans including most pregnant and lactating women ( 55 ), thus underscoring the need to increase awareness among health professionals and consumers regarding choline ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the nutrient quantities available in the national food supply and matched them with the nutritional requirements to inform food policies that can tackle the food insecurity and malnutrition concerns regarding the current diets. Most such studies have focused on just calories (18)(19)(20) or a couple of nutrients (21)(22)(23) while others have investigated the sufficient production of a limited number of macro and micronutrients (16,24,25). Only a few studies have considered the comprehensive nutritional factors involved (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%